2014
DOI: 10.5539/gjhs.v7n1p154
|View full text |Cite
|
Sign up to set email alerts
|

Erectile Dysfunction Among Male Hypertensives in a Tertiary Health Facility in South-West Nigeria

Abstract: Introduction:Erectile dysfunction (ED) has been associated with hypertension and some other chronic diseases. There are few studies on ED in Nigerian male hypertensives and ED appears to be under-reported. We sought to determine the prevalence of ED among hypertensive and normotensive men and to assess the association of demographics, hypertension, antihypertensive medications and other risk factors with erectile function.Methods:A comparative cross sectional study was conducted among male adult hypertensive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
9
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 19 publications
(25 reference statements)
4
9
0
1
Order By: Relevance
“…In this study, the odds of having erectile dysfunction was 4.8 times higher for patients aged between 50 and 60 years, and 5.2 for those aged between 60 and 70 years. These results are similar to those of Fafiolu et al in Nigeria, who found that the risk of erectile dysfunction was multiplied by 3 in hypertensive patients aged above 65 years [9].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this study, the odds of having erectile dysfunction was 4.8 times higher for patients aged between 50 and 60 years, and 5.2 for those aged between 60 and 70 years. These results are similar to those of Fafiolu et al in Nigeria, who found that the risk of erectile dysfunction was multiplied by 3 in hypertensive patients aged above 65 years [9].…”
Section: Discussionsupporting
confidence: 91%
“…These results are similar to those obtained by a study in Thailand, who had a fourfold increase in the prevalence erectile dysfunction in patients with hypertension for more than 5 years [8]. This finding can be explained by the progression of atherosclerosis and endothelial dysfunction with increasing duration and severity of hypertension [9].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…ED prevalence rates as high as that reported in this study have been documented among patients with chronic illnesses. 21 22 23 However, lower figures have been reported in individuals without chronic illnesses. 3 7 24 25 The wide variation in the prevalence of ED in these studies may be due to differences in methodologies, participant selection, and subjective experiences.…”
Section: Discussionmentioning
confidence: 99%
“…A study done by Fafilou and colleagues [24] showed that men aged 45 years, or more were 3 times more likely to have ED compared to men aged less than 45 years. The variability of our study from others is due to the difference in comparison group where men aged 55 years and above were compared to men aged 18-39 years while in massachusettes [25], the comparison was between men aged 40 and 70 years and in Fafilou's study [24], the comparison was between those aged less than 45 to those of 45 or more years. In spite of comorbidities associated with age, there is decrease in sexual function among men as they age which explains the higher prevalence of ED [26].…”
Section: Discussionmentioning
confidence: 98%